High-strength concrete with good durability and preparation method thereof
By adding specific components to high-strength concrete and optimizing its microstructure, the problem of insufficient durability of concrete is solved, and its durability and strength are significantly improved, meeting the high requirements for concrete performance in modern buildings.
Patent Information
- Application Number
- CN202411492818.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
High-strength concrete is susceptible to chemical erosion and freeze-thaw cycles in actual engineering environments, resulting in insufficient durability, reduced structural strength, and threatening building safety and service life.
By adding fly ash, mineral powder, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to the concrete, the microstructure of the concrete is optimized and its density, anti-seepage and crack resistance are enhanced.
It significantly improves the durability and strength of concrete, extends the service life of building structures, reduces maintenance costs, and improves the overall performance of materials.
Smart Images

Figure BDA0005100520020000071 
Figure BDA0005100520020000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building material preparation, and in particular to high-strength concrete with good durability and a preparation method thereof. Background Art
[0002] Concrete, as an indispensable cornerstone of modern architecture, is directly related to the safety and stability of building structures. For a long time, high-strength concrete has become the preferred material for large-scale projects such as high-rise buildings, bridges, and tunnels due to its high strength, high hardness, and excellent mechanical properties. However, with the deepening of engineering practice and the complexity of the building use environment, the performance requirements for concrete materials have also reached a new level. People have gradually realized that simply pursuing high strength is not enough to meet all the requirements of modern buildings for the performance of concrete materials.
[0003] In actual engineering environments, concrete faces complex and ever-changing challenges: harmful gases, salts, and acidic substances in the air will chemically corrode the concrete, erode its surface, and gradually penetrate into the interior, weakening its structural strength; in cold regions, repeated freeze-thaw cycles will cause water to freeze and expand inside the concrete, thus causing damage to the internal structure of the concrete and weakening its structural strength. Therefore, the lack of durability often leads to gradual damage, performance degradation, and even eventual failure of concrete structures during long-term use, which seriously threatens the safety and service life of the building.
[0004] Therefore, in order to ensure the long-term safety of building structures, improving the durability of concrete has become an urgent and important task in the field of building materials science research. Summary of the invention
[0005] In order to overcome the defect of insufficient durability of high-strength concrete, the present application provides a high-strength concrete with good durability and a preparation method thereof. The concrete prepared in the present application can not only significantly improve the durability of the concrete and extend the service life of the building structure, but also maintain the high-strength characteristics of the concrete.
[0006] In the first aspect, the present application provides a high-strength concrete with good durability using the following technical solution: A high-strength concrete with good durability comprises the following components in parts by weight: 240-280 parts of cement, 54-65 parts of fly ash, 90-108 parts of mineral powder, 631-737 parts of sand, 1030-1203 parts of stone, 128-152 parts of water, 5.7-6.8 parts of water reducing agent, 1.9-2.3 parts of sodium polyacrylate, 1.6-2.0 parts of sodium tetraborate and 3.3-3.9 parts of dodecyl glucoside.
[0007] In the above technical scheme, this application not only reduces the amount of cement and the production cost of concrete by adding admixtures composed of fly ash and mineral powder to concrete, but also can further enhance the density and impermeability of concrete due to their micro-filling effect and volcanic ash activity. The addition of water reducer can greatly reduce the water-cement ratio of concrete, promote the densification of the internal structure of concrete, reduce the number of pores in concrete, and thus improve the mechanical strength and impermeability of concrete, laying a solid foundation for improving the strength and durability of concrete. The addition of three admixtures, sodium polyacrylate, sodium tetraborate and dodecyl glucoside, can further significantly improve the strength and durability of concrete. Among them, sodium polyacrylate, as a high molecular polymer, can enhance the cohesiveness of concrete, fill and seal the microscopic pores of concrete. This mechanism of action complements the water reducer to jointly improve the anti-permeability and strength of concrete; sodium tetraborate can slow down the hydration rate of concrete, reduce concrete temperature cracks, and further optimize the pore structure of concrete, reduce the number of harmful pores such as large pores and connected pores in concrete, thereby further improving the anti-permeability performance of concrete; finally, dodecyl glucoside can improve the workability of concrete, reduce the interfacial tension between concrete mortar and aggregate, and make the bonding between the various components of concrete tighter, thereby further improving the mechanical strength of concrete. More importantly, dodecyl glucoside can further refine the pore structure of concrete, increase the proportion of small pores and closed pores in concrete, and reduce the shrinkage of concrete on the basis of improving the microstructure of concrete by sodium polyacrylate and sodium tetraborate, thereby further improving the crack resistance of concrete and improving the mechanical strength and durability of concrete.
[0008] Preferably, the mass ratio of sodium polyacrylate, sodium tetraborate and dodecyl glucoside is 2.1:1.8:3.6.
[0009] In the above technical scheme, the present application further optimizes the synergistic cooperation among sodium polyacrylate, sodium tetraborate and dodecyl glucoside by further limiting the mass ratio of sodium polyacrylate, sodium tetraborate and dodecyl glucoside to 2.1:1.8:3.6. Sodium polyacrylate, sodium tetraborate and dodecyl glucoside act on concrete from different mechanisms of action, significantly optimize the microstructure of concrete, improve the airtightness of concrete, improve the anti-penetration and anti-erosion properties of the concrete, thereby further improving the strength and durability of concrete, and further improving the comprehensive performance of concrete.
[0010] Preferably, the high-strength concrete with good durability also includes 11.3-13.6 parts of biochar.
[0011] In the above technical solution, the present application further improves the durability of concrete by introducing biochar into concrete. Biochar, as a natural porous material, has an extremely high specific surface area and good adsorption properties. Its addition to concrete can effectively improve the durability of concrete, because the porous structure of biochar can adsorb corrosive substances such as chloride ions and sulfates, thereby reducing the erosion of these substances on the internal structure of concrete. In addition, the addition of biochar can also improve the thermal conductivity of concrete, reduce the temperature change inside concrete, reduce cracks caused by temperature stress, further improve the crack resistance of concrete, and further improve the durability of concrete.
[0012] Preferably, the biomass charcoal is obtained by first drying the straw and then heating it to 500-600° C. in an inert atmosphere and subjecting it to a carbonization reaction.
[0013] In the above technical scheme, the biochar prepared from straw has a higher specific surface area and can provide more adsorption sites. At the same time, the microporous structure produced by its carbonization process can effectively adsorb and fix the moisture inside the concrete, reduce the migration of moisture inside the concrete, thereby reducing the damage to the concrete structure caused by freeze-thaw cycles, further enhancing the anti-permeability of the concrete, and further improving the durability of the concrete.
[0014] Preferably, the water reducer is a polycarboxylic acid type high efficiency water reducer.
[0015] In the above technical solution, the polycarboxylic acid type high-efficiency water reducing agent has excellent water reducing performance and dispersibility, and can significantly reduce the water-cement ratio of concrete, thereby improving the density and mechanical properties of concrete. Its unique molecular structure enables it to form a stable adsorption layer on the surface of cement particles, effectively preventing the aggregation of cement particles, thereby improving the fluidity of concrete, so that the concrete still has good working performance at a low water-cement ratio.
[0016] Preferably, the stone is a granite crushed stone with a particle size between 5-25 mm.
[0017] Preferably, the fineness modulus of the sand is 2.9.
[0018] In the above technical solution, the present application further ensures the mechanical properties and durability of the concrete by limiting the stone to granite crushed stone blocks with a particle size between 5-25 mm and limiting the fineness modulus of the sand to 2.9.
[0019] In a second aspect, the present application provides a method for preparing high-strength concrete with good durability using the following technical solution: A method for preparing high-strength concrete with good durability comprises the following steps: Step 1: Evenly mix water, water reducing agent, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to obtain a liquid mixture; evenly mix the remaining raw materials to obtain a dry mix; Step 2: Add the dry mix to the liquid mixture and stir until the mixture is evenly mixed to obtain high-strength concrete with good durability.
[0020] In the above technical scheme, the present application can prepare a kind of durable and high-strength concrete through the above steps. The concrete exhibits excellent mechanical properties and durability in practical engineering applications, meets the high requirements of modern buildings for concrete performance, can effectively extend the service life of building structures, and reduce the maintenance costs of building structures, and has significant economic benefits and social value.
[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. This application reduces the amount of cement, improves the microstructure of concrete, and enhances the density and impermeability of concrete by adding fly ash and mineral powder to concrete through micro-filling effect and volcanic ash activity. By adding a water reducer, the water-cement ratio of concrete is reduced, the microstructure of concrete is further improved, and a solid foundation is laid for the durability of concrete.
[0022] 2. This application adds three admixtures, namely sodium polyacrylate, sodium tetraborate and dodecyl glucoside, to concrete. Through the synergistic effect of sodium polyacrylate, sodium tetraborate and dodecyl glucoside, the microstructure of concrete is optimized, thereby further significantly improving the strength and durability of concrete. DETAILED DESCRIPTION
[0023] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0024] Example 1 A high-strength concrete with good durability comprises 260kg of cement, 60kg of fly ash, 100kg of mineral powder, 684kg of sand, 1116kg of stone, 140kg of water, 6.2kg of water reducing agent, 2.1kg of sodium polyacrylate, 1.8kg of sodium tetraborate and 3.6kg of dodecyl glucoside.
[0025] Among them, the cement is P·||52.5R cement, which was purchased from Guangdong Conch Hongfeng Cement Co., Ltd.
[0026] Among them, the fly ash is || grade fly ash.
[0027] Among them, the mineral powder is S95 grade mineral powder.
[0028] Among them, the sand has a fineness modulus of 2.9 and a grading zone of ||.
[0029] Among them, the stone is granite with a particle size of 5-25mm, produced in Changlu Building Materials.
[0030] Among them, the water reducer is MT-2800 polycarboxylic acid type high-efficiency water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0031] Among them, sodium polyacrylate was purchased from Guangzhou Qiongqi Bioengineering Co., Ltd., CAS number: 9003-04-7.
[0032] Among them, sodium tetraborate was purchased from Dongguan Mosi Chemical Raw Materials Co., Ltd., CAS No.: 1303-96-4.
[0033] Among them, dodecyl glucoside was purchased from Hubei Xinghengye Technology Co., Ltd., CAS No.: 11615-47-9.
[0034] The method for preparing high-strength concrete with good durability comprises the following steps: Step 1: Evenly mix water, water reducing agent, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to obtain a liquid mixture; evenly mix cement, fly ash, mineral powder, sand and stone to obtain a dry mixture.
[0035] Step 2: Add the dry mix to the liquid mixture and stir until the mixture is evenly mixed to obtain high-strength concrete with good durability.
[0036] Example 2 A high-strength concrete with good durability, which is different from Example 1 in that it includes 260kg cement, 60kg fly ash, 100kg mineral powder, 684kg sand, 1116kg stone, 140kg water, 6.2kg water reducer, 2.1kg sodium polyacrylate, 1.8kg sodium tetraborate, and 3.6kg dodecyl glucoside.
[0037] The method for preparing high-strength concrete with good durability comprises the following steps: Step 1: Evenly mix water, water reducing agent, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to obtain a liquid mixture; evenly mix cement, fly ash, mineral powder, sand and stone to obtain a dry mixture.
[0038] Step 2: Add the dry mix to the liquid mixture and stir until the mixture is evenly mixed to obtain high-strength concrete with good durability.
[0039] Example 3 A high-strength concrete with good durability, which is different from Example 1 in that it includes 260kg cement, 60kg fly ash, 100kg mineral powder, 684kg sand, 1116kg stone, 140kg water, 6.2kg water reducer, 2.1kg sodium polyacrylate, 1.8kg sodium tetraborate, and 3.6kg dodecyl glucoside.
[0040] The method for preparing high-strength concrete with good durability comprises the following steps: Step 1: Evenly mix water, water reducing agent, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to obtain a liquid mixture; evenly mix cement, fly ash, mineral powder, sand and stone to obtain a dry mixture.
[0041] Step 2: Add the dry mix to the liquid mixture and stir until the mixture is evenly mixed to obtain high-strength concrete with good durability.
[0042] Example 4 A high-strength concrete with good durability, which is different from Example 1 in that it also includes 12.7 kg of biochar.
[0043] The method for preparing biochar comprises the following steps: Step s1: Take the straw, cut it into short sticks of 1-2 cm, and dry it.
[0044] Step s2: gradually heating the straw to 500° C. in a nitrogen atmosphere to carbonize the straw, and obtaining biochar after the carbonization reaction is completed.
[0045] The method for preparing high-strength concrete with good durability comprises the following steps: Step 1: Evenly mix water, water reducing agent, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to obtain a liquid mixture; evenly mix cement, fly ash, mineral powder, sand, stone and biochar to obtain a dry mixture.
[0046] Step 2: Add the dry mix to the liquid mixture and stir until the mixture is evenly mixed to obtain high-strength concrete with good durability.
[0047] Example 5 A high-strength concrete with good durability, which is different from Example 2 in that it also includes 11.3 kg of biochar.
[0048] The method for preparing biochar comprises the following steps: Step s1: Take the straw, cut it into short sticks of 1-2 cm, and dry it.
[0049] Step s2: gradually heating the straw to 600° C. in a nitrogen atmosphere to carbonize the straw, and obtaining biochar after the carbonization reaction is completed.
[0050] The method for preparing high-strength concrete with good durability comprises the following steps: Step 1: Evenly mix water, water reducing agent, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to obtain a liquid mixture; evenly mix cement, fly ash, mineral powder, sand, stone and biochar to obtain a dry mixture.
[0051] Step 2: Add the dry mix to the liquid mixture and stir until the mixture is evenly mixed to obtain high-strength concrete with good durability.
[0052] Example 6 A high-strength concrete with good durability, which is different from Example 3 in that it also includes 13.6 kg of biochar.
[0053] The method for preparing biochar comprises the following steps: Step s1: Take the straw, cut it into short sticks of 1-2 cm, and dry it.
[0054] Step s2: gradually heating the straw to 550° C. in a nitrogen atmosphere to carbonize the straw, and obtaining biochar after the carbonization reaction is completed.
[0055] The method for preparing high-strength concrete with good durability comprises the following steps: Step 1: Evenly mix water, water reducing agent, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to obtain a liquid mixture; evenly mix cement, fly ash, mineral powder, sand, stone and biochar to obtain a dry mixture.
[0056] Step 2: Add the dry mix to the liquid mixture and stir until the mixture is evenly mixed to obtain high-strength concrete with good durability.
[0057] Example 7 A high-strength concrete with good durability, which is different from Example 1 in that the water reducing agent is replaced by a naphthalene-based high-efficiency water reducing agent.
[0058] Among them, naphthalene-based high-efficiency water reducer was purchased from Jinan Zhiheng Zhiyuan Chemical Technology Co., Ltd., item number: 022-07-06-25.
[0059] Comparative Example 1 A high-strength concrete, which is different from Example 1 in that an equal amount of sodium polyacrylate is replaced by polyvinyl alcohol.
[0060] Among them, the CAS number of polyvinyl alcohol is: 9002-89-5.
[0061] Comparative Example 2 A high-strength concrete, which is different from Example 1 in that sodium tetraborate is replaced by sodium acetate, wherein the CAS number of sodium acetate is 127-09-3.
[0062] Comparative Example 3 A high-strength concrete, which is different from Example 1 in that dodecyl glucoside is replaced by sodium dodecyl sulfate.
[0063] Among them, the CAS number of sodium dodecyl sulfate is: 151-21-3.
[0064] Comparative Example 4 A high-strength concrete, which is different from Example 1 in that sodium polyacrylate, sodium tetraborate and dodecyl glucoside are not added.
[0065] Performance Testing The apparent porosity of concrete blocks prepared from the concrete of the above-mentioned embodiments and comparative examples was tested, and the testing method was as follows: Performance test test sample: Concrete blocks prepared from the concrete of the above-mentioned embodiments and comparative examples were subjected to standard curing for 28 days.
[0066] Water absorption test: Take a 150mm*150mm*150mm concrete test block, drill a concrete core sample with a diameter of 75mm and a height of 75mm, dry it at 105℃ for 72h, weigh it, record it as m1, then immerse the test block completely in water until the mass is constant, wipe off the surface moisture after taking it out, weigh it again, record it as m2. The water absorption calculation formula is: water absorption = (m2-m1) / m1*100%.
[0067] Compressive strength test: Use a pressure testing machine to test the compressive strength of concrete test blocks with a size of 150mm*150mm*150mm, and operate in accordance with GB / T 50081-2016 "Standard Test Method for Mechanical Properties of Ordinary Concrete".
[0068] Chloride ion resistance test: Use a concrete chloride ion flux meter to conduct flux testing on concrete test blocks with a diameter of 100mm and a height of 100mm. Operate in accordance with the flux method standard of GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" and measure the 6h flux.
[0069] Freeze-thaw cycle test: freeze-thaw cycle test was carried out in accordance with GB / T 50082-2009 "Standard for test methods for long-term performance and durability of ordinary concrete". Concrete test blocks with dimensions of 100mm×100mm×400mm were placed in a cyclic freeze-thaw environment of -18℃ to +5℃. The number of cycles was 200. After the cycle, the mass loss rate was measured. Mass loss rate = (initial mass - mass after cycle) / initial mass * 100%.
[0070] The above performance test results are shown in Table 1.
[0071] Table 1: Combined with the analysis of the above performance test results, it can be seen that the concrete samples of Examples 1 to 7 performed well in terms of water absorption, compressive strength, electric flux and mass loss rate, which shows that the use of water reducers and surfactants significantly improves the durability and strength of concrete, and the further addition of biochar can better optimize the durability and strength of concrete.
[0072] Specifically combined with Example 1 and Comparative Examples 1-4, the difference between Example 1 and Comparative Examples 1-4 is that Comparative Examples 1, 2, 3 and 4 replace sodium polyacrylate, sodium tetraborate and dodecyl glucoside, respectively, or do not add these three raw materials at all. As can be seen from Table 1, the concrete sample of Example 1 performs well in terms of water absorption, compressive strength, electric flux and mass loss rate. This shows that the role of sodium polyacrylate, sodium tetraborate and dodecyl glucoside in concrete is irreplaceable, and they work together on the microstructure of concrete to improve its durability and strength.
[0073] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength concrete with good durability, characterized in that: The invention comprises the following components in parts by weight: 240-280 parts of cement, 54-65 parts of fly ash, 90-108 parts of mineral powder, 631-737 parts of sand, 1030-1203 parts of stone, 128-152 parts of water, 5.7-6.8 parts of water reducing agent, 1.9-2.3 parts of sodium polyacrylate, 1.6-2.0 parts of sodium tetraborate and 3.3-3.9 parts of dodecyl glucoside.
2. The high-strength concrete with good durability according to claim 1, characterized in that: The mass ratio of the sodium polyacrylate, sodium tetraborate and dodecyl glucoside is 2.1:1.8:3.
6.
3. The high-strength concrete with good durability according to claim 1, characterized in that: Also included are 11.3-13.6 parts of biochar.
4. The high-strength concrete with good durability according to claim 3, characterized in that: The biomass charcoal is obtained by drying the straw first, then heating it to 500-600° C. in an inert atmosphere, and then subjecting it to a carbonization reaction.
5. The high-strength concrete with good durability according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid type high efficiency water reducing agent.
6. The high-strength concrete with good durability according to claim 1, characterized in that: The stones are granite crushed stones with a particle size between 5 and 25 mm.
7. The high-strength concrete with good durability according to claim 1, characterized in that: The fineness modulus of the sand is 2.
9.
8. A method for preparing high-strength concrete with good durability as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Evenly mix water, water reducing agent, sodium polyacrylate, sodium tetraborate and dodecyl glucoside to obtain a liquid mixture; evenly mix the remaining raw materials to obtain a dry mix; Step 2: Add the dry mix to the liquid mixture and stir until the mixture is evenly mixed to obtain high-strength concrete with good durability.